Kinerja Karyawan Ditinjau dari Kepuasan Kerja, Kecerdasan Emosional dan Stres Kerja - Rahmadani, Sari; Moeins, Anoesyirwan; Yulasmi (SAFE-Network, 2020)
This study aims to determine how much influence job satisfaction, emotional intelligence, and work stress on employee performance at PT. Padang Broad Bay. The method of collecting data through surveys and distributing questionnaires. The sample was 144 respondents and the analytical method used was regression analysis and correlation analysis. Based on the results of multiple regression analysis, the equation Ŷ = 21.790 + 0.256X1 + 0.615X2 - 0.482X3 is obtained. There is a positive and significant effect between job satisfaction (X1) on employee performance (Y), with a tcount of thitung 3.697 or a significantly smaller level than alpha (0,000 <0.05). Then there is a positive and significant effect between emotional intelligence (X2) on employee performance (Y), with a tcount of thitung 8.426 or a significantly smaller level than alpha (0,000 <0.05). Furthermore there is a negative and significant effect between work stress (X3) on employee performance (Y), with t hitung -3,697 or a significant level smaller than alpha (0,000> 0.05). Finally there is a significant influence between job satisfaction (X1), emotional intelligence (X2) and work stress (X3) together on employee performance (Y). There is also a strong relationship between each of these variables with a count of fhitung 75.486 or significantly smaller levels from alpha (0,000 <0.05).